Preparing for the behavior-based interview : how to get the job you want - Fitz-water, Terry L. (Crisp Pub. Menlo ParkUS, 2001)
Advises job-seekers on aspects of preparation for an interview including researching the organization; and preparing an effective resume with cover letter. Advocates the P-A-R-T-N-E-R technique for creating a positive image at the interview. Presents 6 categories of questions commonly asked by interviewers; as well as a sample of behavioral criteria i.e. actual skill requirements, on which an interviewee may be evaluated e.g. time management, decision making, leadership, written skills, managing change. Coaches both on how to answer interviewer's questions; and how to ask questions to interviewers. Advises on follow-up strategies.\n